2018
DOI: 10.1111/jmp.12393
|View full text |Cite
|
Sign up to set email alerts
|

Characterization ofCampylobacter jejuni, Campylobacter upsaliensis,and a novelCampylobacter sp. in a captive non‐human primate zoological collection

Abstract: Background:The aim of this study was to longitudinally investigate the prevalence and characterization of Campylobacter spp. from non-human primates primate (NHP) with a history of endemic diarrhea housed at Como Park Zoo.Methods: Fecal samples from 33 symptom-free NHP belonging to eight different species were collected weekly for 9 weeks. Species-level characterization and phylogenetic analysis of isolates included biochemical testing and 16S rRNA sequencing.Results: Campylobacter spp. were isolated from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 52 publications
(69 reference statements)
0
3
0
Order By: Relevance
“…Average nucleotide identity (ANI) and digital DNA-DNA hybridization (dDDH) analysis using pyani (version 0.2.10) ( 10 ) and the Genome-to-Genome Distance Calculator (version 2.1; accessed 3 April 2020) ( 11 ), respectively, confirmed that all the genomes were novel Campylobacter species. Also, ANI and dDDH analysis determined that Campylobacter species strain MIT 12-5580 from lemurs and Campylobacter species strain MIT 19-121 from marmosets are both the same species as Campylobacter species strain MIT 12-8780 from the white-faced saki (GenBank accession number QHLL01000000 ) ( 12 ).…”
Section: Announcementmentioning
confidence: 99%
“…Average nucleotide identity (ANI) and digital DNA-DNA hybridization (dDDH) analysis using pyani (version 0.2.10) ( 10 ) and the Genome-to-Genome Distance Calculator (version 2.1; accessed 3 April 2020) ( 11 ), respectively, confirmed that all the genomes were novel Campylobacter species. Also, ANI and dDDH analysis determined that Campylobacter species strain MIT 12-5580 from lemurs and Campylobacter species strain MIT 19-121 from marmosets are both the same species as Campylobacter species strain MIT 12-8780 from the white-faced saki (GenBank accession number QHLL01000000 ) ( 12 ).…”
Section: Announcementmentioning
confidence: 99%
“…Due to NHP’s high genomic similarities and close evolutionary relationships to humans, and similar gut flora detected in developing countries, the risk of zoonotic transfer of pathogenic strains of bacteria like Campylobacter is highly probable [ 16 , 17 ]. Previous studies have detected presence of the bacteria in captive NHPs in the United States [ 18 ], New Zealand [ 19 ], and in Kenya [ 15 ]. Presence of pathogenic strains of the bacteria in healthy and asymptomatic monkeys [ 3 ] poses even higher risk of zoonotic spillover through direct physical contact or indirectly as a potential source of environmental contamination by fecal matter [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Due to NHP’s high genomic similarities and close evolutionary relationships to humans, and similar gut flora detected in developing countries, the risk of zoonotic transfer of pathogenic strains of bacteria like Campylobacter is highly probable [14,15]. Previous studies have detected presence of the bacteria in captive NHPs in the United States [16], New Zealand [17], and in Kenya [13]. Presence of pathogenic strains of the bacteria in healthy and asymptomatic monkeys[1] poses even higher risk of zoonotic spillover through direct physical contact or indirectly as a potential source of environmental contamination by fecal matter [18].…”
Section: Introductionmentioning
confidence: 99%